Non-disclosure of tuberculosis diagnosis by patients to their household members in south western Uganda - Nyangoma, Miria; Bajunirwe, Francis; Atwine, Daniel (PLoS ONE, 2020)
Background: Tuberculosis (TB) non-disclosure by adult patients to all household members is a setback to TB control efforts. It reduces the likelihood that household contacts will seek early TB screening, initiation on preventive or curative treatment, but also hinders the implementation of infection controls and home-based directly observed treatment. Therefore, the purpose of this study was to determine the level of TB non-disclosure, its predictors and the effects of disclosure among adult TB patients in Uganda. Methods: We conducted a cross-sectional study at a large regional referral hospital in Mbarara, southwestern Uganda. Questionnaires were administered to collect patients’ sociodemographic and their TB disclosure data. Non-disclosure was considered if a patient did not reveal their TB diagnosis to all household members within 2weeks post-treatment initiation. Univariate and multivariate logistic regression models were fitted for predictors of non-disclosure. Results: We enrolled 62 patients, 74% males, mean age of 32 years, and median of five people per household. Non-disclosure rate was 30.6%. Post-disclosure experiences were positive in 98.3% of patients, while negative experiences suggestive of severe stigma occurred in 12.3% of patients. Being female (OR 6.5, 95% CI: 1.4–29.3) and belonging to Muslim faith (OR 12.4, 95% CI: 1.42–109.1) were significantly associated with TB non-disclosure to household members. Conclusions: There is a high rate of TB non-disclosure to all household members by adult patients in rural Uganda, particularly among women and Muslim patients. Interventions enhancing TB disclosure at household level while minimizing negative effects of stigma should be developed and prioritized
Keywords: Tuberculosis; Diagnosis; Household members; Uganda; Screening; Curative treatment